Enhanced L-theanine production through semi-rational design of γ-glutamylmethylamide synthetase from Methylovorus mays - Fan, Chao; Qi, Jiakun; Cong, Yunhan; Zhang, Chunzhi (Enzyme and microbial technology, 2024)
The thermal instability of γ-glutamylmethylamide synthetase (GMAS) from Methylovorus mays has imposed limitations on its industrial applications, affecting both stability and activity at reaction temperatures. In this study, disulfide bridges were introduced through a combination of directed evolution and rational design to enhance GMAS stability. Among the variants that we generated, M12 exhibited a 1.46-fold improvement in relative enzyme activity and a 6.23-fold increase in half-life at 40℃ compared to the wild-type GMAS. Employing variant M12 under optimal conditions, we achieved the production of 645.7 mM (112.49 g/L) L-theanine with a productivity of 29.3 mM/h, from 800 mM substrate in an ATP regeneration system. Our strategy significantly enhances the biosynthesis efficiency of L-theanine by preserving the structural stability of the enzyme during the catalysis process. [Display omitted] •The designed potential disulfide bond was introduced into the structure of GMAS and played an active role.•The variants of GMAS were obtained with obviously improved thermal stability.•Fed-batch catalysis strategy resulted in the highest titer and productivity of L-theanine production till now.